Kemandirian Pengadilan Dalam Proses Penegakan Hukum Pidana Menuju Sistem Peradilan Pidana Yang Bebas Dan Bertanggung Jawab - Rusli Muhammad (Fakultas Hukum Universitas Islam Indonesia, 2009)
This research discusses problems on judicial independence in relation to the effort the criminal law enforcement. There are two basic problem in this study, first, how judicial independence in the context of criminal law enforcement is, what the influential factors behind it are and what implication causes are. Second, how the effort made for the reformation of judicial independence toward independence and responsible criminal judicial systems.The approach used for this reseaach is socio legal studies and systems appoarch with philosophical appoach as a complement. Data were collected by interview and distributing questioners, data collected were analyzed using discriptive analytical methods. The law of the degree of judicial independence was caused by miscellanies internal and external factors. Internal factors aimed are factors in the body of system which directly interrelated with judicial system. Whereas external factors are factors which lie out side judicial system.Key words: judicial independence, law enforcement, restructurisation, revitalization of judicial and reform to regulation